The impact of the Japanese clinical guidelines on the clinical management of patients with acute cholecystitis. Issue 6 (August 2013) - Shinya, Satoshi; Yamashita, Yuichi; Takada, Tadahiro
Abstract Background/purpose The Japanese clinical guidelines for treating acute cholecystitis (AC), proposed in 2005, provide criteria not only for diagnosis, but also for management depending on the severity of the disease. The aim of this study was to assess how the Japanese guidelines for AC have impacted the clinical situation in Japan. Methods A postal questionnaire was sent to the councillors of the Japanese Society of Abdominal Emergency Medicine three times to ascertain the impact of the Japanese guidelines for AC. We surveyed 291 councillors one year before publication of the guidelines (2004), 279 councillors one year after publication (2006), and 191 councillors six years after publication (2011). Results The response rate was 72.5 % one year before publication of the guidelines, 51.9 % one year later and 69.1 % six years after publication. Early cholecystectomy was used by 41.7 % of the respondents one year before publication, while 57.3 % of the respondents used this treatment one year after publication and 62.3 % of the respondents used it six years after publication. Laparoscopic cholecystectomy was used by 79.1 % of the respondents one year before the guidelines were published, while 87.3 % of the respondents used it one year after publication and 90 % of the respondents reported its use six years after publication. Conclusions The Japanese guidelines for AC are increasingly used and have changed the clinical management of patients with AC. The use of early and laparoscopic cholecystectomy for treating patients with AC has been increasingly adopted in Japan.